Weight-loss interventions and levonorgestrel intrauterine system implantation for early-stage endometrial cancer and atypical endometrial hyperplasia to reduce perioperative risk of severely obese patients - Roze Isono-Taniguchi; Hiroshi Tsubamoto; Kayo Inoue; Tomoko Ueda; Shinichiro Saeki; Yumi Takimoto; Yu Wakimoto; Hiroaki Shibahara (Wolters Kluwer Medknow Publications, 2023)
Endometrial cancer (EC) and atypical endometrial hyperplasia (AEH) are associated with obesity, which increases the perioperative morbidity and surgical difficulties in laparoscopic and robotic surgery. Weight-loss interventions (WLIs) are likely to reduce morbidity; however, delayed surgery may cause cancer progression. To minimize the tumor progression, levonorgestrel intrauterine system (LNG-IUS) with minimal side effects was used until the planned surgery. During 2016 and 2021, we conducted preoperative management of WLI using LNG-IUS for seven highly obese women with a body mass index (BMI) ≥35 kg/m2 who had AEH and EC with Grade 1 and no myometrial invasion on magnetic resonance imaging. In three of the seven patients, the BMI decreased by more than 5. Two patients with AEH achieved remission after LNG-IUS placement and requested conservative management. Five patients with EC underwent laparoscopic hysterectomy, without perioperative complications.